2022
DOI: 10.1186/s12873-022-00747-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing conveyance of older adults with minor head injury by paramedics to the emergency department: a multiple methods study

Abstract: Background Head injury (HI) in older adults due to low-energy falls result in a substantial number of emergency department (ED) attendances. However, mortality associated with minor HI is very low. Reducing conveyance to hospital is important for older adults and is a priority for the National Health Service (NHS). Therefore, paramedics are required to make accurate decisions regarding conveyance to the ED. This study used routine data and semi-structured interviews to explore the factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There is limited research on older adults presenting to the ambulance service with head injuries. Nicholson et al [ 9 ] interviewed paramedics (n = 10) on the factors associated with conveyance decision-making; paramedics remarked that the lack of appropriate alternative care pathways, wound management and stringent guidelines make it challenging to non-convey older adults with a head injury. Our study found that older age and cognitive impairment were associated with non-conveyance, perhaps a surrogate marker for frailer older adults where ED services may not be appropriate for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited research on older adults presenting to the ambulance service with head injuries. Nicholson et al [ 9 ] interviewed paramedics (n = 10) on the factors associated with conveyance decision-making; paramedics remarked that the lack of appropriate alternative care pathways, wound management and stringent guidelines make it challenging to non-convey older adults with a head injury. Our study found that older age and cognitive impairment were associated with non-conveyance, perhaps a surrogate marker for frailer older adults where ED services may not be appropriate for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…While this should be interpreted with caution, there may be a place for ED treatment and review which is beyond the scope of ambulance clinicians. Equally, the literature suggests paramedics would rather access alternative care pathways for their older adult head-injured patients, but these services are unavailable [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation